2005
DOI: 10.1080/1355785052000323047
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social support on health, well-being and management of diabetes mellitus: a black South African perspective

Abstract: The study demonstrated that: (1) socio-emotional and tangible support were the underlying dimensions of social support; (2) socio-emotional support is an important determinant of health and well-being; and (3) social support is beneficial for one aspect of diabetes mellitus management, namely, BP control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 42 publications
9
44
0
4
Order By: Relevance
“…Average scores on the health and well-being sub-scales were very similar to those reported previously for South African diabetic patients (Westaway, 2005) and in the US (Stewart et al, 1988). In contrast with previous research, which found that women and African-Americans tended to report poorer health and well-being (Stewart et al, 1988;Westaway et al, 1999), neither race, language, gender nor marital status affected health and wellbeing in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…Average scores on the health and well-being sub-scales were very similar to those reported previously for South African diabetic patients (Westaway, 2005) and in the US (Stewart et al, 1988). In contrast with previous research, which found that women and African-Americans tended to report poorer health and well-being (Stewart et al, 1988;Westaway et al, 1999), neither race, language, gender nor marital status affected health and wellbeing in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…Diabetes self-care is for example more effective when using a family-centered or church-based approach (SamuelHodge et al 2000). Widowed patients have less emotional support and therefore experience more difficulty with the management of diabetes (Westaway et al 2005). When comparing self-efficacy between patients who were married or living together with all other marital status groups, no significant differences were found.…”
Section: Discussionmentioning
confidence: 78%
“…These systems include electronic support groups, Diabetes SA and the support provided at the health clinics and hospitals. In terms of the relationship between employment status and diabetes selfefficacy, Barrett et al (2007) and Westaway et al (2005) found that patients from higher income groups tend to have better health and engage in more regular leisure time physical activity. In this study a similar correlation was found between employment status and high levels of self-efficacy, which tended to approach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the barriers to transportation were not assessed in this study, previous studies found that distance from health facilities was positively correlated to glycaemic control of the subject [88,89]. Other studies have revealed the importance of social support to subject's glycaemic control [90][91][92]. In view of the increasing incidence of diabetes in Malaysia, social support warrants future research as this may be a barrier to subjects attaining glycaemic control.…”
Section: Glycated Haemoglobinmentioning
confidence: 95%